Correlation between Parity, Birth Interval, and the Frequency of Antenatal Care towards the Incidence of Low Birth Weight Babies in RSUD Dr. Mohammad Soewandhie Surabaya - Budiono Budiono; Baksono Winardi; Ristya Sylva Imannia (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
Low Birth Weight (LBW) contributes to 60% to 80% of all neonatal and infant deaths in Indonesia whilst globally, prevalence of LBW is 15.5%, amounting to approximately 20 million LBW infants born each year. According to several previous studies, factors closely related with the incidence of LBW are high birth rates, shorter birth intervals, and low frequency of Antenatal Care (ANC) examinations. The objective of this study was to determine the correlation between parity, birth interval, and the frequency of ANC towards the incidence of LBW babies. This retrospective cross-sectional study using simple random sampling involved 95 mothers in RSUD Dr. Mohammad Soewandhie Surabaya between January and July 2016. Data was collected using medical records and analyzed using logistic regression test with p < 0.05. The result of this research showed there was no correlations between parity and incidence of LBW babies (p=0.162) nor between birth interval and incidence of LBW babies (p=0.574). There was a correlation between frequency of ANC and incidence of LBW babies (p=0.006). The physician should further improve early detection for LBW babies by monitoring high-risk pregnancy mothers routinely.